2018
DOI: 10.1021/acsami.8b18626
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Biomimetic Silk Scaffolds for Improved Cell Migration and Healing of Skin Wounds

Abstract: Improved and more rapid healing of full-thickness skin wounds remains a major clinical need. Silk fibroin (SF) is a natural protein biomaterial that has been used in skin repair. However, there has been little effort aimed at improving skin healing through tuning the hierarchical microstructure of SF-based matrices and introducing multiple physical cues. Recently, enhanced vascularization was achieved with SF scaffolds with nanofibrous structures and tunable secondary conformation of the matrices. We hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 62 publications
5
83
0
Order By: Relevance
“…The stability of the SFN and SFN‐P composite hydrogels was assessed by measuring the rheological behavior under constant frequency over the temperate range of 22–40 °C. [ 12,13,19 ]…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The stability of the SFN and SFN‐P composite hydrogels was assessed by measuring the rheological behavior under constant frequency over the temperate range of 22–40 °C. [ 12,13,19 ]…”
Section: Methodsmentioning
confidence: 99%
“…Nine to ten week old Sparague‐Dawley (SD) adult male rats were used for the in vivo wound experiments. [ 12,13 ] All animal experiments were approved by the Animal Care and Experiment Committee of the Soochow university (approval number 201905A182, 201906A340, and 201907A108, Suzhou, China). Thirty SD rats were randomly distributed to six groups: blank, SFN, SFN‐LP hydrogels, BMSCs in medium, BMSCs blended with SFN hydrogels (SFN‐BMSCs hydrogels), and BMSC‐loaded on LP particles and then blended with SFN hydrogels (SFN‐LP‐BMSCs hydrogels).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the content of silk fibroin in PVA hydrogel may be one of the factors that affect cell morphology. Although silk fibroin hydrogels are beneficial for stem cell growth and differentiation [20,21], and silk fibroin composite scaffolds are also widely studied, such as silk fibroin/chitosan/graphene oxide scaffolds [22] and silk fibroin/chitosan/bioactive glass nanoparticle scaffolds [23]. These studies indicated that the composition and content of silk fibroin in composite scaffolds play an important role in cell morphology and behavior.…”
Section: Discussionmentioning
confidence: 99%